Uma contribuição experimental aos fundamentos da propagação de uma frente de combustão em meio poroso - Monhol, Filipe Arthur Firmino (2015)
The combustion front propagation occurs in a variety of situations and for different industrial purposes. The performance of these processes needs to be improved and at the same time to reduce emission levels to meet the international standards. For this purpose, is needed a certain degree of knowledge of both processes of combustion phenomena. In all situations involving combustion phenomena, the propagation is initiated by a source of heat, and after fuel ignition, combustion front reaches the adjacent fuel. Previous studies have shown the ignition and the combustion front propagation as a complex phenomenon which depends on chemical, thermal and physical processes. This work focuses on the challenges encountered during an empirical approach to analyze the propagation of a combustion front in fixed bed. From the use of simulated fuels, it were analyzed: the influence of fuel composition on the behavior of its ignition, the characteristics of the combustion front propagation (combustion regime, shrinkage of the bed and the front structure) and the influence of fuel ignition in the propagation of the combustion front. It was possible to perform a mapping of ignition behavior of the solid fuel for different compositions. From the results of front propagation, it was found that, basically, three combustion stages occur in the bed: Ignition, Propagation and Oxidation of the remaining fixed carbon. Through gas analysis it was noted that there were two reaction modes present in the bed: reaction limited and oxygen limited. It was obtained than in bed with high content of inert materials, where there is greater stability, there is a greater influence from the ignition to the combustion front. Thus, it was shown how these skills are useful in various applications and industrial processes.